Nursery schools: characterization of heavy metal content in indoor dust / Fairus Muhamad-Darus ... [et al.] - Muhamad-Darus, Fairus; Nasir, Rabiatul Adawiyah; Sumari, Siti Mariam; Ismail, Zitty Sarah; Omar, Nur Aliah (Universiti Teknologi MARA Cawangan Selangor, 2017)
Interior floor dust is found to be one of the major pathways of childhood exposure to indoor air pollutants. This study aims to carry out a general survey of heavy metals (Al, Ba, Cr, Cu, Fe, Ni and Pb) contamination at selected nursery school buildings in Shah Alam, Selangor and to study their relationship with the surrounding environment. The samples were collected using a brush and a plastic dust pan, after which the samples were digested using the wet digestion method. The heavy metal concentration was determined by inductively coupled plasma - optical emission spectrometer (ICPOES). The results show that the heavy metal concentrations at nursery school building were in the range 901.2 - 1510.0, 13.3 - 76.7, 12.0 - 22.6, 22.2 - 42.7, 1489.0 - 7919.0, 5.5 -14.4, 13.2 - 64.6, 93.3 - 220.4mg kg-1 for Al, Ba, Cr, Cu, Fe, Ni and Pb respectively. The heavy metal concentration in the investigated areas followed the order Fe > Al > Zn > Pb > Ba > Cu > Cr > Ni. Principal Component Analysis (PCA) was carried out to ascertain the possible contributing factors towards the metal concentrations and thereby determine which metals have a common origin. PCA analysis indicated that three factors indicated source of mixed origin including mobile vehicle, street dust and natural sources.